PENGEMBANGAN E-MODUL BERBASIS ANDROID UNTUK MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS SISWA SMP IT ABDURRAB PEKANBARU - Syafrudin, Syafrudin; Arief, Zainal Abidin; Waspodo, Muktiono (JURNAL TEKNOLOGI PENDIDIKAN, 2023)
This study aims to: (1) produce an Android-based E-module forimprove students' mathematical connection ability, (2) analyze the feasibility of the product as well(3) determine the effectiveness of product development. This study uses a modeldevelopment of Dick & Carey integrated with Hannafian & Peck. This research is doneat Abdurrab Pekanbaru IT Middle School in the 2022/2023 school year. The research subjects are paramaterial experts, instructional design experts and learning media experts who come from lecturers andTeacher. The sample in this study was class VII A1 as the experimental class and class VIIA2 as control class. The object of research is an Android-based math E-module. Resultsresearch shows the quality of the developed E-module belongs to the very categoryfeasible with the average test results of learning media experts, learning material experts and designinstructional is 92.35%. While the t_count value is 2.07 and the t_table value is at the levelsignificant 5% of 2.01 makat_count> t_table or 2.07> 2.01, so h_adi is accepted and h_0rejected. This means that there is a significant difference in the ability of the mathematical connection betweenexperimental class students and control class students. This shows that the E-moduleAndroid-based is feasible, effective and can improve connection capabilitiesstudent mathematics.